Pro-angiogenic approach for skeletal muscle regeneration - Floriano, Juliana Ferreira [UNESP] (2022)
The angiogenesis process is a phenomenon in which numerous molecules participate in the stimulation of the new vessels' formation from pre-existing vessels. Angiogenesis is a crucial step in tissue regeneration and recovery of organ and tissue function. Muscle diseases affect millions of people worldwide overcome the ability of skeletal muscle to self-repair. Pro-angiogenic therapies are key in skeletal muscle regeneration where both myogenesis and angiogenesis occur. These therapies have been based on mesenchymal stem cells (MSCs), exosomes, microRNAs (miRs) and delivery of biological factors. The use of different calls of biomaterials is another approach, including ceramics, composites, and polymers. Natural polymers are use due its bioactivity and biocompatibility in addition to its use as scaffolds and in drug delivery systems. One of these polymers is the natural rubber latex (NRL) which is biocompatible, bioactive, versatile, low-costing, and capable of promoting tissue regeneration and angiogenesis. In this review, the advances in the field of pro-angiogenic therapies are discussed.